(untitled) (Research, Society and Development, 2020)
Carbonic anhydrase II (CA II) is involved with the acid-base homeostasis of tissue. This study aims to evaluate the effect of traumatic dental occlusion (TDO) by means of CA II expression in osteoclasts and osteocytes (near the lamina dura and in the centre of alveolar bone septum), in the periodontal ligament (PDL) and in lining cells (periosteum). For this study, 50 male Wistar rats aged seven weeks were divided into 2 groups: Loaded and Unloaded group. The study periods were 2, 5, 7, 14 and 21 days. The Mann-Whitney U test for quantitative, and the Chi-square test for semi-quantitative analyses were used for group comparison, along with Bonferroni’s post-hoc test. Statistically significant differences between the groups were observed in the number of osteoclasts in the lamina dura (days 5, 7 and 21); the alveolar bone septum (days 2 and 7); osteocytes near the lamina dura (days 2, 5, 7 and 14); and in the centre of the alveolar bone septum (days 2, 5, 7 and 14). There were also differences between-group in CA II expression in the lining cells on days 7 and 14. TDO increases CA II expression in osteoclasts, osteocytes, the PDL and lining cells of the periosteum. Clinical Relevance: Traumatic dental occlusion stimulates higher cells activity of the alveolar bone at short (lamina dura) and long (centre of alveolar bone and periosteum) distances.